The Globalization of Martyrdom : Al Qaeda, Salafi Jihad, and the Diffusion of Suicide Attacks - Moghadam, Assaf (Baltimore Johns Hopkins University Press, 2008)
"This groundbreaking volume examines the rise and spread of suicide attacks over the past decade. Sorting through 1,270 terror strikes between 1981 and 2007, Assaf Moghadam attributes their recent proliferation to the mutually related ascendance of al Qaeda and its guiding ideology, Salafi Jihad, an extreme interpretation of Islam that rejects national boundaries and seeks to create a global Muslim community.
Include Index, Bibliography and Notes
Keywords: Terrorism--Religious aspects--Islam -- Jihad -- Suicide bombings